Conservation and divergence of vulnerability and responses to stressors between human and mouse astrocytes - Jiwen Li (Nature Portfolio, 2021)
Astrocytes are important players in brain development, homeostasis, and disease. Here, the authors compare the transcriptional profiles of human and mouse astrocytes. They report species-specific susceptibility to oxidative stress and response to hypoxic and inflammatory conditions.